Functional Hybrid Nanopaper by Assembling Nanofibers of Cellulose and Sepiolite. (15th August 2017) - González del Campo, M. Mar; Darder, Margarita; Aranda, Pilar; Akkari, Marwa; Huttel, Yves; Mayoral, Alvaro; Bettini, Jefferson; Ruiz‐Hitzky, Eduardo
Abstract: Functional heterofibrous hybrid materials are prepared in an integrative approach from aqueous dispersions of nanofibrillated cellulose and sepiolite by applying high shear homogenization and ultrasound irradiation. Both types of nanofibers remain physically cross‐linked forming homogeneous and very stable high‐viscosity gels that can be shaped as films and considered as "hybrid nanopapers" as well. The presence of sepiolite modifies the surface roughness of the films resulting from the casting process, which can be rendered hydrophobic, as the hydrophilic characteristics of both components resulted modulated. In addition, these fibrous hybrid systems can benefit from the properties provided by the two components, such as mechanical behavior, surface properties, and chemical reactivity. Moreover, further assembly of these hybrid nanopapers to other particulate solids, such as carbon nanotubes, magnetite, or ZnO nanoparticles, results in multifunctional hybrid nanopapers, opening a versatile way for developing other numerous organic–inorganic materials of interest in diverse applications. Abstract : Herein, a functional hybrid nanopaper by assembling nanofibers of cellulose and sepiolite is demonstrated . The cross‐assembly between two kinds of nanofibers of organic and inorganic nature through mechanical and sonomechanical processes results in nanostructured biohybrids showing ability toward further functionalization giving rise to functional materials with tunable properties and diverse potential applications.